Distinct phenotypes associated with increasing dosage of the PLP gene: implications for CMT1A due to PMP22 gene duplication - Anderson, Thomas J.; Klugmann, Matthias; Schneider, Armin; Nave, Klaus-Armin (Annals of the New York Academy of Sciences, 1999)
ABSTRACT: Increased dosage of the proteolipid protein (Plp) gene causes CNS disease (Pelizaeus-Merzbacher disease [PMD]), which has many similarities to disorders of the PNS associated with duplication of the peripheral myelin protein-22 (PMP22) gene locus. Transgenic mice carrying extra copies of the wild-type Plp gene provide a valid model of PMD. Variations in gene dosage can cause a wide range of phenotypes from severe, lethal dysmyelination through late-onset demyelination. A predilection for different fiber diameters may occur within the various phenotypes with dysmyelination being more obvious in large fibers and late-onset degeneration predominantly affecting small fibers. Although the frequency of apoptotic oligodendrocytes is increased with high gene dosage, the number of mature oligodendrocytes appears adequate. Oligodendrocytes in the dysmyelinated CNS express a range of genes typical of mature cells, yet are unable to assemble sufficient myelin. Oligodendrocytes contain abnormal vacuoles and stain intensely for PLP and other proteins such as MAG. The findings suggest that with high gene dosage much of the PLP, and possibly other proteins, is missorted and degraded in the lysosomal system.
Gesehen am 02.06.2017